Home Care of Poinsettias - Stevens, Alan B.; Albrecht, Mary; Kimmins, R. Kent (My University, 1995)
This publication describes how to care for poinsettias after an individual brings one home.
MF521_1995_05
Keywords: MF521; Lawn and Garden; Flowers; MF